Proceedings of the Tenth ACM International Conference on Web Search and Data Mining 2017
DOI: 10.1145/3018661.3018669
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Factorized Network Modeling for Evolutionary Network Analysis

Abstract: The problem of evolutionary network analysis has gained increasing attention in recent years, because of an increasing number of networks, which are encountered in temporal settings. For example, social networks, communication networks, and information networks continuously evolve over time, and it is desirable to learn interesting trends about how the network structure evolves over time, and in terms of other interesting trends. One challenging aspect of networks is that they are inherently resistant to param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…As T and d are small and constant compared to |V |, in total, the time complexity of tNodeEmbed is O(|V | 2 ). The lowest time complexity among the other temporal state-of-the-art methods is of O(|V | 2 ) [10, 34,55], while the highest is of O(|V | 2 |E|) [56]. We conclude our method is at the lower bound of time complexity compared to the state-of-the-art methods.…”
Section: Time and Space Complexitymentioning
confidence: 88%
See 1 more Smart Citation
“…As T and d are small and constant compared to |V |, in total, the time complexity of tNodeEmbed is O(|V | 2 ). The lowest time complexity among the other temporal state-of-the-art methods is of O(|V | 2 ) [10, 34,55], while the highest is of O(|V | 2 |E|) [56]. We conclude our method is at the lower bound of time complexity compared to the state-of-the-art methods.…”
Section: Time and Space Complexitymentioning
confidence: 88%
“…Temporally Factorized Network Modeling (TFNM) [55]: this method applies factorization before collapsing, by generalizing the regular notion of matrix factorization for matrices with a third 'time' dimension. Given T adjacency matrices A 1 , .…”
Section: Baselinesmentioning
confidence: 99%
“…They take the correlation between the quasi-local similarity measures and temporal evolutions of link occurrences information into account by using NARX for multivariate time series forecasting. Yu et al developed a novel temporal matrix factorization model to explicitly represent the network as a function of time [44]. They provided results for link prediction as a specific example and showed that their model performs better than the state-of-the-art techniques.…”
Section: Related Workmentioning
confidence: 99%
“…He and Chen [14] propose an algorithm for dynamic community detection in temporal networks, which takes advantage of community information at previous time steps. Yu, Aggarwal, and Wang [42] present a model-based matrix factorization for link prediction and also for community prediction. However, their work uses only links for the prediction process.…”
Section: Introductionmentioning
confidence: 99%